JURIDICAL ANALYSIS OF RIGHTS REGISTRATION PROCESS ON LAND AND OWNERSHIP STATUS TO CONFIRM LEGAL ASSURANCE: STUDYRESEARCH IN THE AGENCY OFFICE NATIONAL LAND BATAM CITY - Al Hakim, Hafiz; Aminah, Point; I, Idham; Milanie, Feby; Saifannur, Andri Saifannur (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
Land registration aims to guarantee legal certainty and certainty of land rights. By holding land registration, the parties concerned can easily find out the status of the legal status of the particular land they are dealing with, their location, area and boundaries. And also as a condition for the implementation of orderly land administration. The purpose of this study is to find out the legal arrangements regarding the process of registering land rights and ownership status in order to confirm legal certainty and how to implement, constraint factors and solutions to problems that occur in the community. This research uses normative legal research methods. The normative method is writing that uses primary materials or data. In normative legal research, library materials in the form of basic data which in the study are classified as secondary data. Secondary data can include primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that the legal arrangements regarding the responsibilities of the Batam City National Land Agency in the process of registering land rights have been carried out well by the Batam City National Land Agency in order to realize legal certainty for the people of Batam City. However, in carrying out their duties there are still obstacles in the process of registering land rights in Batam City because of the imbalance of authority with the Batam Concession Agency as the holder of land management rights in Batam City. So, the solution is expected to have special regulations regarding this so that the process of registering land rights in Batam City can run in accordance with the laws and regulations.